Respuesta :
Answer:
[tex]27[/tex]
Explanation:
To solve this, we must follow the PEMDAS rule:
Parenthesis
Exponents
Multiply
Divide
Add
Subtract
So lets start on the left equation:
Since parenthesis is first, we must do this:
(150 - 168 + 24)
168 + 24
==> 192
192 - 150
==> 42
So right now we have:
([tex]8^{2}[/tex] + 42 - [tex]5^{2}[/tex]
Do the exponents now:
[tex]8^{2} = 64[/tex] and [tex]5^{2}[/tex] = 25
64 + 42 - 25
64 + 42
==> 106
106 - 25
==> 81
So now we have 81 for the left equation, now for the right:
(3 × 5 - 3 × 2²)
Exponents first:
[tex]2^{2} = 4[/tex]
(3 × 5 - 3 × 4)
3 * 5
==> 15
3 * 4
==> 12
15 - 12
==> 3
So now we should be with:
81 divided by 3
81 ÷ 3
==> 27